Time, Man, Society and "Ode On A Grecian Urn" in William Faulkner's As I Lay Dying, Go Down, Moses and Light In August - Foong, Ting-Ting (My University, 1994)
Much has been written on the references to John Keats' "Ode On A Grecian Urn" in William Faulkners novels. Critical analysis has dealt mainly with the utilization of images and symbols from the "Ode" in Faulkner's fiction without any sense of a thematic pattern connecting each fictional work. This thesis also examines Keatsian references in Faulkner's novels, in particular, As I Lay Dying, Go Down. Moses and Light In August. However, the approach of this thesis is to regard these three novels as interrelated in that they comprise a multi-faceted meditation on John Keats' "Ode". This meditation involves abstracting imagistic, symbolic and thematic references from Keats' poem in an examination of the theme of artistic and temporal transcendence. Faulkner's references are inverted with a wry, darkly ironic tone that questions the function and status of romantic idealism in the modem world. Together, As I Lay Dying, Go Down. Moses and Light In August comprise a treatise on the spiritual 'degeneration of today's society and comments on the direction in which society is travelling.
Keywords: English Language and Literature; English Language and Literature